Analisis Kerusakan Perkerasan Jalan dengan Metode PCI (Pavement Condition Index): Studi Kasus : Jalan Sugio - Tlanak - Heni Purwati Ningsih; Lily Oktavia; Miftahur Rohman (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The Sugio–Tlanak Road Section, Sugio District, Lamongan Regency, is a vital transportation infrastructure as it connects interregional activities, both in economic, social, and community mobility aspects. This road is the main route used by various types of vehicles, from light vehicles to heavy vehicles with quite high traffic intensity. This condition has a significant impact on the quality of the road pavement, as indicated by the presence of various types of damage at several points, such as cracks, potholes, and road surface deformation. Therefore, a comprehensive evaluation is needed to determine the level of road damage as a basis for consideration in planning maintenance and repairs. This study uses two assessment methods, namely the Bina Marga method and the Pavement Condition Index (PCI). The Bina Marga method assesses road conditions based on the Surface Distress Index (SDI) value obtained from direct identification in the field. The evaluation results show that the road condition on the Sugio–Tlanak section is classified as severely damaged at 60%, moderately damaged at 30%, and good condition at only 10%. Meanwhile, the PCI method provides results in the form of more detailed quantitative values. The analysis results obtained an average PCI score of 58.6, which is included in the Fair category. A comparison of the two methods shows that the Bina Marga method has advantages in terms of speed and ease of implementation, but its assessment is relatively subjective. In contrast, the PCI method provides more accurate and measurable results because it uses a quantitative approach with clear damage condition parameters. Therefore, although the Bina Marga method can still be used for rapid assessments in the field, the PCI method is more recommended as a basis for technical decision-making in planning road maintenance and quality improvement programs.